Family Law, Maqāṣid al-Sharīʿah, and State Resilience: A Comparative Study of Legislative Reform in Muslim Jurisdictions - Aghbalou, Omar (Mazahibuna: Jurnal Perbandingan Mazhab, 2026)
The instability of family institutions in contemporary Muslim societies is often reductively framed as a matter of individual morality. However, domestic stability constitutes a fundamental juridical determinant for the realization of the comprehensive concept of security (al-amn) and macro-level state resilience. Despite this, much of the existing academic literature remains predominantly focused on philosophical and normative approaches to the protection of the five essential necessities (al-darūriyyāt al-khams), without sufficiently explaining how these principles are operationalized within concrete family law frameworks and legislative policies across diverse Muslim jurisdictions. This study addresses this gap by adopting a juridic-comparative approach, analyzing the paradigmatic shift from classical jurisprudence to modern legal codification in Morocco and other Muslim countries, particularly in relation to the protection of life (nafs) and progeny (nasl) within the domestic sphere. The findings demonstrate that family security is not merely a moral construct but a legal-institutional one that requires strengthened statutory protections, enhanced accountability mechanisms for legal guardianship, and the transformation of the ethical value of trust (amānah) into binding legal obligations to effectively safeguard marital rights and ensure child protection. By incorporating this comparative dimension, the study proposes an original theoretical framework for the renewal of Islamic legislation at the global level, integrating the protection of domestic rights with broader agendas of social reform and state resilience in the context of globalization.